Hexokinase 2 drives glycogen accumulation in equine endometrium at day 12 of diestrus and pregnancy. Issue 1 (December 2017) - Bramer, Sarah; Macedo, Alysson; Klein, Claudia
Abstract Background Secretion of histotroph during the prolonged pre-implantation phase in mares is crucial to pregnancy maintenance, manifested as increased embryonic loss in mares with age-related endometrial degeneration. Glycogen content of uterine histotroph is higher during the progesterone-dominated phase of the estrous cycle in mares, but regulatory mechanisms are not well understood. Methods mRNA expression of glycogen-metabolizing enzymes (HK1, HK2, GSK3B, GYS1, PEPCK, PKM, PYGM) in endometrial samples were compared among mares in anestrus, estrus, and at Day 12 of diestrus and pregnancy. In addition, hexokinase 2 (HK2) activity was assessed using a colorimetric assay. Results HK2 was the key regulator of glycogen accumulation during diestrus and pregnancy; hexokinase transcript abundance and enzyme activity were significantly higher during diestrus and pregnancy than estrus and anestrus. In addition, despite similar relative transcript abundance, hexokinase activity was significantly greater in the pregnant versus diestrous endometrium. Therefore, we inferred there was regulation of hexokinase activity through phosphorylation, in addition to its regulation at the transcriptional level during early pregnancy. Based on immunohistochemistry, HK2 was localized primarily in luminal and glandular epithelial cells, with weaker staining in stromal cells. Conclusion Among glycogen metabolizing enzymes identified, expression of HK2 was significantly greater during the progesterone-dominated phase of the cycle.